Changes to iso standards and their effects on machinery noise declarations - Keith, Stephen E.; BIy, Stephen H. P. (Canadian Acoustics, 2011)
The article describes recent improvements in the basic ISO standards for measurement of machinery noise and how they can affect the ease of determination, or the reliability, of machinery noise declarations. Improvements to the ISO standards could be incorporated into potential revisions of the Canadian voluntary standard for machinery noise declarations. These should aid conformance to the Health Canada recommendation that machinery sold in Canada includes standardized noise emission declarations in sales literature and instructions for use. Each standard now has an annex with a detailed listing of typical uncertainty components. These components can be quantified by measurements, experience, general knowledge, or manufacturers specifications. In addition to the detailed uncertainty budget, the standards also include a simplified uncertainty budget.